Analisis Pembangunan Zona Lalu Lintas dengan Standard Deviation Control Kepadatan Area Terbangun Studi Kasus: Kabupaten Klungkung, Provinsi Bali - Pribadi, Ocky Soelistyo; Nurhadi, Muhammad; Hermawan, Bobby Agung (Institut Transportasi dan Logistik Trisakti, 2023)
Traffic movement occurs in the context of space, it is necessary to prepare the research area with the construction of traffic zones. This work requires a series of activities, complex data, and many considerations, in order to produce a concept to support the data collection stage of the origin of the trip. This study aims to build traffic zones using a new logic, namely by controlling the standard deviation value of the built area density variable. The author attempts to replace the variable commonly used in the preparation of traffic zones, namely “land use type” and strives for the value to be as “homogeneous as possible”. This variable is fairer to use, considering that in an area there will also be open space, which is not inhabited by humans. The formulation of the problem is how is the standard deviation control method used to construct traffic zones in the Klungkung Regency case study? This method will focus on the technique of constructing traffic zones where the standard deviation value of the density of the built area will be smaller when compared to the initial value when the existing traffic zone was formed directly from the village area. The results of the analysis get a total of 26 traffic zones, with a standard deviation value of the variable density of the built area is 2049. this value is lower than when using the village administrative area directly, namely 3294, and it is said that the design of the 26 zones has fulfilled the principle of zone homogeneity.